Bringing the benefits of sorghum genomics to Africa - Kelemu, Segenet; Gebrekidan, B.; Harvey, Jagger J.W. (Springer, 2013)
Sorghum was the first indigenous African crop to have a completed genome sequence. This provides an invaluable tool for understanding sorghum traits genetically and identifying useful molecular markers. The challenge is to extract relevant information to improve the diverse complex traits of sorghum including drought tolerance, disease and pest resistance, and overall yield. The promise of sorghum to improve food security and help lift millions of Africans out of poverty provides a moral imperative for investing in its improvement. Therefore, we must critically and objectively assess all available resources and coordinate our efforts for the benefit of Africans.